2008
DOI: 10.1063/1.2956668
|View full text |Cite
|
Sign up to set email alerts
|

Stretched-exponential a-Si:H∕c-Si interface recombination decay

Abstract: The electronic properties of hydrogenated amorphous silicon ͑a-Si: H͒ relax following stretched exponentials. This phenomenon was explained in the past by dispersive hydrogen diffusion, or by retrapping included hydrogen motion. In this letter, the authors report that the electronic passivation properties of intrinsic a-Si: H/crystalline silicon ͑c-Si͒ interfaces relax following a similar law. Carrier injection dependent a-Si: H / c-Si interface recombination calculations suggest this originates from amphoteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
116
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 26 publications
12
116
0
Order By: Relevance
“…2 In recent years, a-Si:H layers also garnered significant attention, thanks to their excellent crystalline silicon (c-Si) surface passivation properties, even when only a few nm thin. [3][4][5][6][7][8] This property is exploited with remarkable success for passivating-contact fabrication in silicon heterojunction (SHJ) solar cells, [9][10][11][12][13][14][15][16][17][18][19][20][21][22] with reported conversion cell efficiencies as high as 26.3%. 23 For any solar cell technology, an important criterion for ultimate device performance is its stability under prolonged light exposure.…”
mentioning
confidence: 99%
“…2 In recent years, a-Si:H layers also garnered significant attention, thanks to their excellent crystalline silicon (c-Si) surface passivation properties, even when only a few nm thin. [3][4][5][6][7][8] This property is exploited with remarkable success for passivating-contact fabrication in silicon heterojunction (SHJ) solar cells, [9][10][11][12][13][14][15][16][17][18][19][20][21][22] with reported conversion cell efficiencies as high as 26.3%. 23 For any solar cell technology, an important criterion for ultimate device performance is its stability under prolonged light exposure.…”
mentioning
confidence: 99%
“…25 The a-Si:H/c-Si interface itself is also strongly affected by the hydrogen content and structure of the a-Si:H film. 10,26 Since hydrogen in the plasma plays such a critical role, it is clear that D can be a physically relevant parameter for assessing the quality of the passivating layers. A detailed description of the link between depletion and passivation through hydrogen chemical reactions is, however, beyond the scope of this paper.…”
mentioning
confidence: 99%
“…It has been shown that a-Si:H can provide excellent passivation of c-Si surfaces. [7][8][9][10] However, to produce highefficiency devices, it is crucial to control the properties of the a-Si:H layers during deposition. This task is usually difficult for heterojunction solar cells, because the layers thicknesses have to be kept very low, in the order of 10-15 nm.…”
mentioning
confidence: 99%
“…time dependent) hydrogen diffusion [3], or from retrapping included hydrogen motion [4]. For the a-Si:H(i) / c-Si interface, based on the latter interpretation, it has been argued that the annealing induced passivation may originate from a transfer of hydrogen from a higher hydride state in the a-Si:H film (close to the interface) to a monohydride cSi surface state [5]. Consequently, the a-Si:H(i)/c-Si interface passivation is likely due to chemical surface state passivation, rather than a field effect.…”
Section: Intrinsic A-si:h Film Passivationmentioning
confidence: 99%